Developing Emerging Leaders to Support Team-Based Primary Care. Issue 4 (October 2019) - Coleman, Katie; Wagner, Edward H.; Ladden, Maryjoan D.; Flinter, Margaret; Cromp, DeAnn; Hsu, Clarissa; Crabtree, Benjamin F.; McDonald, Sarah
Abstract : Teams are increasingly used to deliver high-quality, accessible primary care, yet few leadership programs support the development of team-based care leadership capabilities. The 12-month Emerging Leaders program presents a prototype for how interdisciplinary training targeting frontline staff might be implemented. Emerging Leaders training included didactic content, mentorship, applied peer-to-peer learning, and personal leadership development components delivered in person and virtually. Attendance at training events was high. Nominators and Emerging Leaders noted improvements in knowledge, skills, and attitudes of program participants. Forty percent of participants went on to promotions or new jobs.